iTRAQ-Based Comparative Proteomic Analysis of Seedling Leaves of Two Upland Cotton Genotypes Differing in Salt Tolerance - Gong, Wenfang; Xu, Feifei; Sun, Junling; Peng, Zhen; He, Shoupu; Pan, Zhaoe; Du, Xiongming (Frontiers in Plant Science, 2017)
Cotton yields are greatly reduced under high salinity stress conditions, although cotton is considered a moderately salt-tolerant crop. Understanding at the molecular level how cotton responds to salt stress will help in developing salt tolerant varieties. Here, we combined physiological analysis with isobaric tags for relative and absolute quantitation (iTRAQ)-based proteomics of seedling leaves of 2 genotypes differing in salinity tolerance to 200 mM (18.3 dS/m) NaCl stress. Salt stress produced significant stress symptoms in the sensitive genotype Nan Dan Ba Di Da Hua (N), including lower relative water and chlorophyll contents and higher relative electrolyte leakage and Na+/K+ ratio in leaf samples, compared with those in the tolerant genotype Earlistaple 7 (Z). A total of 58 differentially abundant salt-responsive proteins were identified. Asp-Glu-Ala-Asp (DEAD)-box ATP-dependent RNA helicase 3 and protochlorophyllide reductase were markedly suppressed after salt treatment, whereas the phosphate-related differentially abundant proteins (DAPs) phosphoethanolamine N-methyltransferase 1 and 14-3-3-like protein E were induced, and all these proteins may play significant roles in salt stress. Twenty-nine salt-responsive proteins were also genotype specific, and 62.1% and 27.6% of these were related to chloroplast and defense responses, respectively. Based on the Arabidopsis thaliana protein interaction database, orthologs of 25 proteins showed interactions in Arabidopsis, and among these, a calmodulin protein was predicted to have 212 functional partners. In addition, the Golgi apparatus and calcium may be important for salt secretion in cotton. Through integrative proteome and transcriptome analysis, 16 DAPs were matched to differentially expressed genes and verified using qRT-PCR. On the basis of these findings, we proposed that some proteins related to chloroplast, ATP, ribosomal, and phosphate metabolism as well as to the Golgi apparatus and calcium may play key roles in the short-term salt stress response of cotton seedling leaves.